An Exploratory Study of Career Development and Advancement of Women towards and into Executive Level in the Canadian Federal Public Service - Gray, Lynda (Université d'Ottawa / University of Ottawa, 2011)
Women working in the Canadian Federal Public Service (CFPS) face complex issues and competing demands. However, despite challenges such as obtaining further education, managing home responsibilities, and dealing with workplace issues, some have also developed and managed successful careers. Problems highlighted within literature on career development for women relate to the nature of women’s lives with their many transitional points, in which personal and organizational factors inextricably intertwine. The purpose of this qualitative research study was to explore the career development and advancement of women towards and into entry executive level positions within the Canadian Federal Public Service (CFPS). Three research questions guided this inquiry: 1) How have personal factors influenced career development and advancement of women in the CFPS towards and into pre-executive and entry executive levels? 2) How have organizational factors influenced their career development and advancement? and 3) How have personal and organizational factors combined to influence their career development and advancement? This research was grounded in a social constructivist paradigm which guided the research both ontologically and epistemologically. Schwandt (1994) contends that “objective knowledge and truth is a result of perspective. Knowledge and truth are created, not discovered” (p. 125). The inquiry attempted, therefore, to understand women’s complex career development processes from a holistic perspective through their career life stories. Ten women at the pre-executive or entry executive level from various departments within the CFPS took part in the study. Data collection was carried out mainly through a series of three semi-structured interviews. The findings of the study describe how participants’ personal dispositions, formal education, and home lives (personal factors) influenced their career development and advancement. In addition, it was found that the organization’s culture of long hours, its support for learning, participants’ organizational networks, and superiors’ contributions (organizational factors) also influenced women’s careers. This study contributes to our understanding of women’s career development, thereby providing important insights for future research. The study may have implications for CFPS policymakers, career counsellors, universities responsible for educating future career counsellors, as well as for individual women themselves, and perhaps even men.
Keywords: women; career development; Canada; Canadian federal public service; career advancement; career